Structural characterization, derivatization, and bioactivities of secondary metabolites produced by termite-associated Streptomyces lannensis BYF-106 - Jun Wu; Miao Zhang; Jian Tao; MengRu Liu; JianHao Xiong; TaoShan Jiang; YaXuan Wang; XiaoHong Li; YueYue Li; CaiPing Yin; ShuXiang Zhang; XinHua Liu; et al. (Microbiology Spectrum)
ABSTRACT Two new C-glycoside angucycline-related analogs, urdamycin Y (1) and grincamycin W (2), as well as eight known metabolites (3–10), were identified from termite-associated Streptomyces lannensis BYF-106 based on global natural products social molecular networking (GNPS). The putative biosynthetic pathways of urdamycin Y (1) and grincamycin W (2) were proposed using bioinformatic analysis of the full genome of S. lannensis BYF-106. In addition, four new derivative compounds (4A, 5A, 6A, and 6B) were synthesized via acetylation and methylation, respectively. Partial compounds were evaluated in vitro for antibacterial, anti-inflammatory, and cytotoxic activities. Vineomycinone B2 (3), fridamycin D (4), and 6-hydroxytetrangulol (5) displayed broad-spectrum antibacterial activities against S. aureus, methicillin-resistant S. aureus, and P. syringae pv. actinidae. Furthermore, urdamycin Y (1) exhibited potent inhibition on NO production, with an IC50 value of 4.8 µM, which was comparable to that of Bay11-7082 with an IC50 value of 2.1 µM. Subsequently, the possible anti-inflammatory mechanism of urdamycin Y (1) was explored by molecular docking simulation. Finally, most of the tested metabolites showed significant cytotoxic activities against HCT-116, HT-29, and A375. Notably, 6-hydroxytetrangulol (5) and the acetyl derivative 5A showed extremely strong cytotoxic activities against HCT-116, with IC50 values of 9.8 and 2.2 µM, respectively. Moreover, 5A showed extremely strong cytotoxic activity against A375 (IC50 <0.2 µM), and the conceivable cytotoxic activity mechanism was also proposed by molecular docking. These findings indicated metabolites of insect-associated S. lannensis BYF-106 might be a potential source for developing new bioactive drugs in food, agriculture, and biomedical fields.IMPORTANCEFrequent attention to soil microorganisms has led to the rediscovery of known compounds. By contrast, insect-associated Streptomyces have been shown to produce a more diverse array of unique bioactive secondary metabolites compared to soil Streptomyces. In our ongoing effort to explore structurally diverse bioactive natural products from termite-associated Streptomyces, we discovered that the strain S. lannensis BYF-106 exhibited potent bioactivity. Chemical investigation of BYF-106 resulted in the isolation of two new C-glycoside angucycline-related analogs: urdamycin Y (1) and grincamycin W (2). In addition, four new derivative compounds (4A, 5A, 6A, and 6B) were synthesized through acetylation and methylation, respectively. Urdamycin Y (1) exhibited a strong inhibitory effect on NO production, and most of the tested metabolites showed significant cytotoxic activity. These findings indicate that the metabolites of BYF-106 may offer promising avenues for the exploration and development of new bioactive drugs.